Qualitative study exploring reintegration of clinical trial participants with HIV to public health services in Johannesburg, South Africa - Samanta Tresha Lalla-Edward; Kelechi Elizabeth Oladimeji; Sibongiseni Thandazani Nxumalo; Bernice Harris; Lizeka Napoles (BMJ Open)
Objective People living with HIV (PLHIV) are often recruited from primary healthcare clinics (PHC) into clinical trials. On trial completion, they are transferred back to the facility for continued care and support in managing their condition, potentially leading to better health outcomes. Because transferring PLHIV back to PHCs post-clinical trials may result in decreased access to specialised care or resources that were available during the trial, this study explored insights into challenges faced during reintegration from clinical trial settings into PHCs and antiretroviral therapy (ART) adherence post-clinical trials.Design This cross-sectional study was conducted using a qualitative research approach. Participants were recruited using purposive sampling.Setting The study was conducted at the Ezintsha Research Centre in Johannesburg, South Africa, between November 2022 and February 2023.Participants The study population consisted of PLHIV who had participated in two clinical trials (DORA and ADVANCE) at the Ezintsha Research Centre in Johannesburg, South Africa.Methods Using a semistructured guide, 12 in-depth interviews were conducted with PLHIV until data saturation was reached. Data were then transcribed verbatim and analysed thematically with MAXQDA software.Results The majority (n=8, 67%) of participants were female, and the average age of all participants was 40 (SD 7.2) years. Two main themes emerged: reintegration from clinical trials to public healthcare and barriers to ART adherence. These themes were further separated into seven subthemes, namely, negative attitude of healthcare workers, poor healthcare service delivery, poor communication to patients, waiting time at healthcare facilities, lack of privacy and confidentiality, mistakes in ART dispensing and bad reception at facilities post-clinical trials.Conclusion Clinical trial sites should cultivate better stakeholder engagement with PHCs to facilitate a smoother transition of research participants, especially PLHIV, back into public healthcare for continued care.